Specific Endonuclease R Fragments of Bacteriophage φX174 Deoxyribonucleic Acid - Edgell, Marshall H. (1972)
The restriction enzyme from Hemophilus influenzae, endonuclease R, cleaves φX174 replicative-form deoxyribonucleic acid (DNA) into at least 13 specific limit fragments. The molecular weights of 12 of the fragments have been estimated by gel electrophoresis and electron microscopy. Using the genetic assay for small fragments of φX DNA, we have shown that we can salvage markers from the endonuclease R φX-RF fragments.